Prevalence and determinants of post-neonatal mortality in East Africa: a multilevel analysis of the recent demographic and health survey - Zegeye, Alebachew Ferede; Asmamaw, Desale Bihonegn; Negash, Wubshet D.; Belachew, Tadele Biresaw; Fentie, Elsa Awoke; Kidie, Atitegeb Abera; Baykeda, Tsegaw Amare; Fetene, Samrawit Mihret; Addis, Banchlay; Maru Wubante, Sisay; Endawkie, Abel; Tamir, Tadesse Tarik (Frontiers in Pediatrics, 2025)
BackgroundOne of the most common measures of society's health is mortality among neonates. Developing and developed countries still differ significantly in neonatal mortality rates. While there are about 18 neonatal deaths worldwide for every 1,000 live births during the first month of life, less is known about neonatal mortality in developing countries, especially in East Africa. Understanding the extent of mortality during the post-neonatal period and its determinants is crucial for developing appropriate policies and strategies that could help solve the issue. Thus, the aim of this study was to identify the prevalence of post-neonatal mortality in East African countries and the factors that are associated with it.MethodsSecondary data analysis was conducted using data from the most recent Demographic and Health Surveys, which included 11 East African countries between 2014 and 2022. A weighted sample of 225,635 live births had been used in the study. STATA/SE 14 was used for data analysis. The multilevel mixed-effects logistic regression model was applied to determine the factors associated with post-neonatal mortality. In the multilevel logistic regression model, significant factors were deemed to be associated with post-neonatal mortality at p-values <0.05. The data were interpreted using the adjusted odds ratio (AOR) and confidence interval (CI). The best-fit model has been found to be the one with the lowest deviance and highest logliklihood ratio.ResultsIn East Africa, post-neonatal mortality was found to be 15 per 1,000 live births. Pregnancy type (AOR = 3.09, 95% CI: 2.30, 4.13), birth weight (AOR = 1.58, 95% CI: 1.25, 2.01), maternal age (AOR = 1.58, 95% CI: 1.32, 1.90), maternal education (AOR = 1.82, 95% CI: 1.14, 2.92), tetanus shots prior to delivery (AOR = 1.23; 95% CI: 1.06–1.42), birth order (AOR = 5.68, 95% CI: 4.48, 7.24), those born in Uganda (AOR = 1.33, 95% CI: 1.03, 1.73), and Burundi (AOR = 1.48, 95% CI: 1.11, 1.98) had the highest odds of post-neonatal death.ConclusionAccording to this study, post-neonatal mortality is higher in developing countries, particularly in East Africa. It was discovered that factors at the individual and community levels associated with post-neonatal mortality. Consequently, focus should be paid to babies born to mothers in the lowest age group, those born of multiple pregnancies, without formal educations, who did not receive tetanus shots prior to birth, and who were born in the first birth order.